Monotonic and cyclic compressive performance of self-monitoring MWCNT/PA12 cellular composites manufactured by selective laser sintering - Muhammad Umar Azam; S Kumar; Andreas Schiffer (Composites Part C: Open Access)
Herein, we experimentally investigate the mechanical and piezoresistive properties of selectively laser-sintered cellular composites under monotonic and cyclic compressive loading. Hexagonal honeycomb structures (HHSs) with relative densities of 20 %, 30 %, and 40 % were 3D printed from a ball-milled nanocomposite powder of multi-walled carbon nanotubes (MWCNTs) and polyamide 12 (PA12) with 0.3 wt.% MWCNTs. The pure PA12 HHSs exhibited lower porosity and superior mechanical properties, including collapse strength, elastic modulus and energy absorption, particularly at higher relative densities (30 % and 40 %). Notably, the specific energy absorption for the PA12 HHSs reached 24 J g⁻¹, under out-of-plane compression at 40 % relative density. Compared to neat PA12, the MWCNT/PA12 HHSs showed a reduction in strength and modulus but demonstrated excellent energy absorption efficiency of up to 53 %. Moreover, MWCNT/PA12 HHSs exhibited exceptional strain-sensing capabilities in the elastic region with gauge factors of up to 25. Cyclic tests showed that the zero-load resistance increased significantly as damage progressed during the collapse phase, highlighting their potential for application in smart, lightweight structures with integrated strain and damage-sensing functionalities.